The first Czechoslovak cipher machine. Issue 3 (4th May 2023) - Antal, Eugen; Zajac, Pavol
Abstract: The Štolba cipher machine was the first Czechoslovak cipher machine used in the army after the mid-1930s, and later in Slovakia during WW2. It had a unique design based on pneumatic transmission and complex stepping rules. We present basic facts about the Štolba machine from documents found in Czech and Slovak archives. Although the machine description was incomplete (and in some cases not accurate), we have been able to reconstruct (a highly probable) encryption algorithm, and develop a method to reconstruct (message) key from a known PC pair. Part of the machine configuration, however, still remains unknown due to the large space of possible settings and the complexity of the algorithm.